Evaluating and selecting criteria and indicators of forest sustainability: a case study on participatory assessment under CBFM in the Philippines - Mendoza, G.A.; Prabhu, Ravi (1999)
This paper describes an application of multi-criteria analysis (MCA) in evaluating and selecting criteria and indicators (C&I) of forest sustainability. The method was applied on a case study involving a forest area managed under the Community-Based Forest Management System of the Department of Environment and Natural Resources. Experience gained from the study indicates that MCA is a suitable tool for the systematic evaluation of C&I including validation of previously developed national set of C&I, modification of the validated set by incorporating other externally generated C&I, and ultimately, prioritization of the C&I according to their perceived importance.